The Identification of the Top Agro Food Keywords in The Star Online Newspaper - Farhan Mohamad Mohsin, Mohamad; Sakira Kamaruddin, Siti; Siraj, Fadzilah; Aini Hambali, Hamirul; Ahmed. Taiye, Mohammed (International Journal of Engineering and Technology, 2018)
News websites produce thousands of articles and the number is growing. To publish up to date breaking news, each news providers apply different styles of journalism and as consequent readers may find different words and concepts used although when reporting a similar event.Â  In this study, we examined the Malaysian online newspaper in order to seek the most regular keywords used in daily online news. To achieve that, the Star Online newspaper was chosen and the news related to Malaysian Agro food industries was selected for mining. During the mining, 173 news articles were scrapped from the website within the time frame of 2008-2017 and the keyword were mine using RAKE algorithm. From the analysis, 51 frequently used agro food related keywords has been identified and fish is the top keyword used in The Star Online. The other popular keywords found were palm oil, rice, fruits, livestock, vegetables, chicken, and crops. It is also noticed that different terms were used to describe similar concept. The indentified keywords can be used to form future agro inventory. In future work, the other Malaysian Online newspaper such as The New Strait Time and The Sun will be further explored and comparison of the top agro food keyword will be made among them.Â Â